Multifactorial Ascites in a Kitten with Chronic Malnutrition - Viviana Anyaputri Tanurahardja; Putu Ayu Sisyawati Putriningsih; I Gusti Made Krisna Erawan (Journal of Applied Veterinary Science And Technology, 2026)
Background: Ascites is a frequent clinical finding in cats, representing an underlying systemic disorder rather than a definitive diagnosis. In pediatric felines, abdominal effusion is commonly associated with Feline Infectious Peritonitis (FIP) or helminthiasis, often causing diagnostic bias toward infectious etiologies. However, non-infectious causes like malnutrition, hepatic dysfunction, and inflammatory processes must be considered, particularly in rescued kittens with uncertain nutritional histories. Purpose: Identification chronic malnutrition as a significant non infectious contributor to ascites in a kitten, emphasizing the necessity of nutritional assessment within a systematic diagnostic approach to improve clinical decision-making. Case(s): A two month old male domestic kitten (0.35 kg) was presented with progressive abdominal distension, alopecia, bilateral distal forelimb swelling, and poor body condition following uncontrolled feeding with nutritionally inadequate wet food. Physical examination identified mild hypothermia and a low body condition score. Hematology showed macrocytic anemia and leukocytosis, while serum biochemistry revealed mild hypoalbuminemia, elevated alanine aminotransferase activity, and reduced calcium and phosphate concentrations. Radiography confirmed free abdominal fluid, and abdominocentesis yielded turbid effusion dominated by degenerate neutrophils. A negative Rivalta Test subsequently reduced the likelihood of FIP. Case Management: Management focused on nutritional correction and supportive intervention. Transition to a high energy, high protein formulation ensured metabolic recovery. Supportive treatment included vitamin B complex injections, hepatoprotective therapy, oral pyrantel pamoate, and empirical amoxicillin targeting suspected suppurative inflammation. Ad libitum water access was provided alongside hydration monitoring. Conclusion: Rapid clinical improvement following nutritional intervention supports malnutrition as a primary factor in ascites development. Integrating nutritional evaluation is essential in the diagnostic workup of ascites in young rescued cats.